Phenotyping and Genotyping of Coagulation Factor V Leiden - Engel, H; Zwang, L; van Vliet, H H D M; Michiles, J J; Stibbe, J; Lindemans, J (Thrombosis and Haemostasis, 1996)
The currently used activated Protein C resistance test demonstrated to be of limited diagnostic value for the detection of the mutant Factor V Leiden. Moreover, this assay is not useful for patients under anticoagulant therapy. A modification of the APC resistance test, applying Factor V deficient plasma is described which demonstrates a specificity and sensitivity of 1.0. The superiority of the modified APC resistance test over the existing APC resistance test was verified by genotyping.For that purpose, the Amplification Refractory Mutation System (ARMS) was applied to the detection of the G to A mutation at position 1691 in the gene encoding coagulation Factor V. The mutation at that position could be easily detected by using each of two allele-specific oligonucleotide primers concomitantly with one common primer in two separate polymerase chain reactions, thereby amplifying a fragment of 186 base-pairs of the Factor V gene.